2021
DOI: 10.5005/jp-journals-10071-23720
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin Monotherapy vs. Combination Therapy for the Treatment of Multidrug-resistant Infections: A Systematic Review and Meta-analysis

Abstract: A bstract Objectives The objective of this review was to compare the effectiveness of Colistin monotherapy and combination therapy for the treatment of multidrug-resistant gram-negative bacterial infections. Data sources PubMed, Cochrane Library. Study eligibility, interventions, and exclusions In this systematic review, we included all retrospective and prospective studies and randomized controlled trials (RCTs) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Given the heterogeneously resistant nature of polymyxins, the combination administration is recommended as the first-line treatment. However, a recent meta-analysis did not observe an advantage of polymyxins combination therapy on multidrug-resistant gram-negative bacterial infections 30. In addition, another meta-analysis suggested that CAZ-AVI in monotherapy or combination therapy for CRE infections demonstrated similar effect on mortality and microbiological cure rates 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the heterogeneously resistant nature of polymyxins, the combination administration is recommended as the first-line treatment. However, a recent meta-analysis did not observe an advantage of polymyxins combination therapy on multidrug-resistant gram-negative bacterial infections 30. In addition, another meta-analysis suggested that CAZ-AVI in monotherapy or combination therapy for CRE infections demonstrated similar effect on mortality and microbiological cure rates 31.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis did not observe an advantage of polymyxins combination therapy on multidrug-resistant gram-negative bacterial infections. 30 In addition, another meta-analysis suggested that CAZ-AVI in monotherapy or combination therapy for CRE infections demonstrated similar effect on mortality and microbiological cure rates. 31 Therefore, both combined and single-drug regimens were included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Combination antimicrobial therapy can afford multiple advantages in the clinical care of patients including providing broad coverage in cases of diagnostic uncertainty, as well as potentially improved efficacy against drug-resistant organisms due to bacterial killing from multiple mechanisms of action. 11,[27][28][29] This therapeutic strategy extends well-beyond ophthalmology and has been widely used to treat a variety of diseases including gastrointestinal infections, HIV, and TB. [30][31][32] Moreover, antibiotic combination therapy is part of management guidelines for several severe infectious diseases such as hospital-acquired, ventilator-associated, and health care-associated pneumonia 33 as well as sepsis and septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Samal et al [22] performed a meta-analysis with similar eligibility criteria as the previously mentioned study [21]. This study included seventeen prospective studies (6 RCTs) and twenty-two retrospective studies.…”
Section: Polymyxin Versus Polymyxin Combination Therapymentioning
confidence: 99%
“…Therefore, we comprehensively summarize published meta-analyses and illustrate the significance and feature of combination therapy as a therapeutic option against MDR pathogens. Table 1 shows a list of studies that reported meta-analyses of antibiotic combinations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%